الأمن الطاقوي في ظل الصراع والتنافس الدولي وفرص تعزيز المكانة الإقليمية دراسة حالة الجزائر، المغرب ونيجيريا - معامير سفيان (جامعة الوادي University Of Eloued, 2024)
تعد الطاقة أساس مخططات التنمية لجميع الدول التي تسعى لتحقيق معدلات نمو عالية والرفع من مؤشرات الأداء الاقتصادي لها، وفي سنة 2022 إبان اندلاع الحرب الروسية الأوكرانية، واستخدام روسيا لامداداتها من الغاز لأوروبا كأداة لإدارة الصراع والضغط الدولي، برز دور أمن الطاقة كأحد مفردات الأمن القومي الحديث، ما دفع أوروبا للبحث عن منافذ ومصادر جديدة للطاقة، على غرار دول شمال أفريقيا التي تبحث عن الفوز بعقود توريد الغاز، أو عقود إنشاء خطوط الأنابيب. وفي هذا الإطار، تهدف هذه الدراسة – ومن منظور أمن الطاقة – إلى تحليل العلاقات الإقليمية بين كل من نيجيريا والجزائر والمغرب، وذلك في سياق سعي كل من الجزائر والمغرب لتكون مركزا إقليميا لنقل وتداول الطاقة. وقد خلصت الدراسة إلى أن أوروبا لن تعتمد على سوق واحدة وأن حصولها على كميات أكبر من الغاز النيجيري في إطار مشروعين منفصلين -يصبان في مصلحة أوروبا ونيجيريا- أقرب للواقع لتأمين إمدادات الطاقة، وأن مشروع خط الأنابيب (نيجيريا – الجزائر) المرتقب يعتبر "المشروع الأكثر جدوى والأقل تكلفة مقارنة بمشروع خط الأنابيب (نيجيريا – المغرب). Energy is the basis of development plans for all countries that seek to achieve high growth rates and raise their economic performance indicators. In the year 2022, during the outbreak of the Russian-Ukrainian war, and Russia’s use of its gas supplies to Europe as a tool for managing conflict and international pressure, the role of energy security emerged as one of the components of modern national security. This prompted Europe to search for new energy outlets, similar to North African countries looking to win contracts to supply and build pipelinesgaz. In this context, this study aims - from the perspective of energy security - to analyze the regional relations between Nigeria, Algeria and Morocco, in the context of Algeria and Morocco's quest to be a regional hub for energy transmission and tradingm.The study concluded that Europe will not rely on a single market and that its access to greater quantities of Nigerian gas under two separate projects is closer to reality to secure energy supplies, and that the upcoming pipeline project (Nigeria - Algeria) is "the most feasible and least expensive project compared to the pipeline project (Nigeria - Morocco).
Energy security in light of conflict, international competition, and opportunities to enhance regional status Case study of Algeria, Morocco and Nigeria
Keywords: أمن الطاقة; غاز; حرب روسيا-أوكرانيا; الجزائر; المغرب; نيجيريا; Energy Security; Gas; Russo-Ukrainian War; Algeria; Morocco; Nigeria